2002
DOI: 10.1093/nar/gkf479
|View full text |Cite
|
Sign up to set email alerts
|

Defects in interstrand cross-link uncoupling do not account for the extreme sensitivity of ERCC1 and XPF cells to cisplatin

Abstract: The anticancer drug cisplatin reacts with DNA leading to the formation of interstrand and intrastrand cross-links that are the critical cytotoxic lesions. In contrast to cells bearing mutations in other components of the nucleotide excision repair apparatus (XPB, XPD, XPG and CSB), cells defective for the ERCC1-XPF structure-specific nuclease are highly sensitive to cisplatin. To determine if the extreme sensitivity of XPF and ERCC1 cells to cisplatin results from specific defects in the repair of either intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
129
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(142 citation statements)
references
References 29 publications
13
129
0
Order By: Relevance
“…These results suggest that the entire NER pathway is not necessary to generate DSB in cells, and that the XPF protein specifically participates in an NER-independent function that is required and probably rate-limiting for DSB formation in human cells. This conclusion is generally in agreement with prior work, which indicated that the NER functions of XPF are distinct from its role in ICL processing [23,47,48]. Our work in human cells corroborates and complements prior work, all in Chinese hamster ovary cells, demonstrating that ERCC1, which normally is in a heterodimeric complex with XPF, is required for the initial incisions and γ-H2AX formation [32], and that XPF and ERCC1 are required for incisions leading to DSB in an in vitro assay [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that the entire NER pathway is not necessary to generate DSB in cells, and that the XPF protein specifically participates in an NER-independent function that is required and probably rate-limiting for DSB formation in human cells. This conclusion is generally in agreement with prior work, which indicated that the NER functions of XPF are distinct from its role in ICL processing [23,47,48]. Our work in human cells corroborates and complements prior work, all in Chinese hamster ovary cells, demonstrating that ERCC1, which normally is in a heterodimeric complex with XPF, is required for the initial incisions and γ-H2AX formation [32], and that XPF and ERCC1 are required for incisions leading to DSB in an in vitro assay [14].…”
Section: Discussionsupporting
confidence: 92%
“…Some precedent for differential processing of chemically distinct ICL exists. Cisplatin forms a small number of ICL and fails to induce DSB in rodent cells [48]. NER processing of psoralen ICL that depends on XPA and other NER proteins to uncouple one strand of the ICL [21,22], followed by translesion synthesis with a bypass polymerase may be one scenario that could account for reduced DSB formation in GM637 cells relative to XP-A cells [11,20,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first step in the complex molecular mechanism of repair of DNA ICLs (McHugh et al, 2001) and the comet assay cannot determine if the repair process has gone to completion and correctly restored the integrity of both strands of the DNA. Mammalian cells defective in the unhooking step of cisplatin interstrand crosslink repair, as measured using the comet assay, include cells bearing mutations in nucleotide excision repair (e.g., XPB, XPD, XPG, ERCC1 and XPF) and homologous recombination (e.g., XRCC2 and XRCC3) (De Silva et al, 2002). Cells defective in ERCC1 are highly sensitive to cisplatin and several groups have investigated the influence of ERCC1 on resistance to platinum chemotherapy (Ferry et al, 2000;Reed, 2005) and suggest that ERCC1 is a good marker for cellular or clinical resistance to these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The method has also been used to measure cisplatin-induced ICLs in vitro (De Silva et al, 2002). In this study, we have used the method to compare the formation and repair (unhooking) of ICL's following ex vivo exposure to cisplatin in tumour cells and normal cells isolated from ovarian cancer patients who were either newly diagnosed, or had been previously treated with platinum-based chemotherapy.…”
mentioning
confidence: 99%
“…The UV5 cell line is defective in the XPD protein, which is involved in NER and crosslink repair [37], but not homologous recombination [38]. Since only the UV4 and not the UV5 cell line was sensitive to ICT2901 and ICT2903, it implicates that homologous recombination is involved in the response to these agents.…”
Section: Repair Of Dna Adducts In Cho Cell Linesmentioning
confidence: 98%